A Strategic Evaluation of Artificial Intelligence for Innovative Libraries in the 21st Century: The Components and Applications (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
Advances in technology have changed things globally, especially in the area of information management, business and governance, so much that the effective use of information technology makes a difference between success and failure. There exist some levels of uncertainty about the future of libraries, occasioned by the competition poised by Google, Amazon, Wikipedia, Myspace etc., which are veritable sources of information. The aim of this study is to evaluate strategically the component and application of Artificial Intelligence (AI) for Innovative Libraries in the 21st Century. From the study is it then concluded that The application of artificial intelligence and machine learning in libraries is an emerging trend that has captured the attention of relevant practitioners and academics. Some advanced AI and ML techniques like pattern recognition and MAS are also being used to ensure library security; user identification; book title recognition; RFID management, and other administration activities. Deep learning, neural network algorithms, convolutional neural networks have also been proved as powerful tools for scholarship, collections discovery, search and analysis. One of the recommendations drawn from the study is that appropriate training should be given to librarians concerning the technical knowhow of the adoption of AI in the library.